Differences In Growth of Two Varieties of Oil Palm(Elaeis guineensis Jacq.) to The Composition of Planting Mediain Prenursery - eddy susanto; lisa mawarni; asil barus (Universitas Sumatera Utara, 2018)
The purpose of this research is to know the difference growth of two varieties of palm oil (Elaeis guineensis Jacq.) on composition media pretax cropping in a nursery. This research have held in the faculty of agriculture land of usu in december 2016 to march 2017 using random design group with two factors .The first factor varieties with two kinds of varieties namely Yangambi and PPKS540 .The second factor media cropping with three types of media cropping namely subsoil, empty fruit bunch, and fibers palm oil. Parameters that observed is high in plant, diameter of the stem, total broad leaves, fresh editorial weights, weights fresh roots, dry weight editorial and weights dried root. The result show that treatment cropping influential media real against tall plant, diameter of the stem, wet editorial weights and weights dry editorial. Where treatment influential real varieties on the parameter weights dried root. And variety of Yangambi (V1).While media cropping best is media cropping subsoil or control ( M0 ).